The means of building digital libraries - Rzheuskiy, Antoniy; Kunanets, Nataliya; Malynovskyi, Ostap (Видавництво Львівської політехніки, 2017)
The information technologies of building electronic libraries are considered. The emphasis is on the application of cloud platforms for the further development of service-oriented library systems.
Keywords: electronic library; full-text document; cloud services; service-oriented library system